(untitled) (Journal Of Educational and Psychological Researches, 2024)
The research aims to investigate the impact of the COVID-19 pandemic on the psychological problems of students at Hashemite University during the academic year 2021–2022. The study used a questionnaire consisting of 60 items and included a random sample of 696 students. The results showed that the level of psychological problems among the students was moderate, with boredom being the highest, followed by loneliness, depression and sadness, eating disorders, obsessive-compulsive disorder, social fears, and finally sleep disorders. No differences in the level of psychological problems were found based on gender or college variables, but differences were found in boredom based on the year of study, with fourth-year students most affected, followed by third-year, then second-year, and finally first-year students, and differences were found based on place of residence in social fears and sleep disorders in favor of village, followed by city, and then camp residents, and family income in loneliness, depression and sadness, boredom, and eating disorders among students in favor of families with income less than (500), followed by (500-1000), and then (1000). The study recommends conducting more research on the psychological problems of university students during the COVID-19 pandemic with different variables in government and private universities